Habit tic deformity of bilateral thumbnails: A dermoscopic view - Anmol Bhargava; Sunanda A Mahajan (Wolters Kluwer Medknow Publications, 2022)
Nail examination is an important aspect of a wholistic dermatological examination, which when overlooked leads to missing out on important and interesting relevant findings. We observed one such typical interesting finding in a patient who presented to the out patient department with characteristic nail changes suggestive of habit tic type of onychotillomania as an incidental finding. Further, dermoscopy of the affected nails showed characteristic features of the same.